2020
DOI: 10.1080/19420862.2020.1792673
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent binding on cells varies between anti-CD20 antibodies and is dose-dependent

Abstract: Based on their mechanism of action, two types of anti-CD20 antibodies are distinguished: Type I, which efficiently mediate complement-dependent cytotoxicity, and Type II, which instead are more efficient in inducing direct cell death. Several molecular characteristics of these antibodies have been suggested to underlie these different biological functions, one of these being the manner of binding to CD20 expressed on malignant B cells. However, the exact binding model on cells is unclear. In this study, the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…This order changed when the stability of cell-bound OBI was studied in the presence of unlabeled antibody in solution: after 2 h the highest percentage of remaining OBI molecules was on P493.6 cells, followed by LCL1.11, Ramos and lastly Daudi cells ( Figure 3E , dashed lines). In agreement with previously obtained data ( 41 ), the binding stability of OFA was not significantly influenced by the presence of equimolar amounts of free antibody in the 10-60 nM range (data not shown). Therefore, the stability of OFA was tested with 60 nM labeled antibody during the association, followed by three-fold molar excess of unlabeled antibody during the dissociation phase.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This order changed when the stability of cell-bound OBI was studied in the presence of unlabeled antibody in solution: after 2 h the highest percentage of remaining OBI molecules was on P493.6 cells, followed by LCL1.11, Ramos and lastly Daudi cells ( Figure 3E , dashed lines). In agreement with previously obtained data ( 41 ), the binding stability of OFA was not significantly influenced by the presence of equimolar amounts of free antibody in the 10-60 nM range (data not shown). Therefore, the stability of OFA was tested with 60 nM labeled antibody during the association, followed by three-fold molar excess of unlabeled antibody during the dissociation phase.…”
Section: Resultssupporting
confidence: 93%
“…A variety of B cell lines such as Raji ( 11 , 23 , 38 , 43 , 44 ), Ramos ( 44 , 45 ), or Daudi ( 11 , 38 , 46 ) are routinely used to study cytotoxic IgG activity directed against CD20. When studying the interaction of CD20-specific mAbs, we previously found that binding to the Burkitt lymphoma cell line Daudi ( 47 ) is most stable for OFA, followed by RTX and least stable for OBI, due to the mAbs engaging in bivalent target binding to differing degrees ( 41 ). To extend our analyses, we evaluated the binding pattern of the three mAbs by real-time interaction analysis on additional human lymphoma B cell lines (the Burkitt lymphoma cell line Ramos ( 48 ) and the lymphoblastoid cell lines P493.6 ( 49 ) and LCL1.11) ( Figures 1A–D ), as well as primary human B cells ( Figure 2A ) purified from human peripheral blood ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ofatumumab has similar binding affinity for CD20 compared to rituximab, it has a slower off rate, resulting in more durable binding and binding stoichiometry that causes closer association of multiple mAb Fc regions which further increases its ability to activate complement [29,[54][55][56][57]. mAb ability to activate complement is determined by target cell membrane ligand density and the ability to generate the hexameric Fc configuration that efficiently activates C1q [55,58]. For example, complement activation by rituximab in CLL, a disease characterized by low cell membrane CD20 density, is considerably less than in other B-cell lymphomas with higher CD20 density such as follicular cell lymphoma.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…mAb that bind ligand epitopes closer to the cell membrane (e.g., ofatumumab) are more likely to mediate membrane capture of activated complement components. Although ofatumumab has similar binding affinity for CD20 compared to rituximab, it has a slower off rate, resulting in more durable binding and binding stoichiometry that causes closer association of multiple mAb Fc regions which further increases its ability to activate complement [ 29 , 54 , 55 , 56 , 57 ].…”
Section: Complement Activation and Cdcmentioning
confidence: 99%